Efficacy and Safety of Omadacycline in Chronic Kidney Disease (CKD) Patients with Acute Bacterial Skin and Skin Structure Infections (ABSSSI): A Subgroup Analysis from the OASIS Tria. (4th October 2017) - File, Thomas M; Cure-Bolt, Nancy; Chitra, Surya; Tzanis, Evan; McGovern, Paul
Abstract: Background: Many antibiotics, including tetracycline, have adverse effects associated with renal insufficiency, necessitating dosage adjustment. Omadacycline (OMC), is a novel, broad-spectrum aminomethylcycline related to tetracyclines. In OASIS, a phase 3 ABSSSI study, intravenous (IV)-to-oral OMC was non-inferior to IV-to-oral linezolid (LZD). Here, we report the efficacy and safety of OMC vs. LZD in patients with stage 1 CKD (CKD-1; GFR ≥ 90 mL/minute) or stage 2/3 CKD (CKD-2/3; GFR = 30–89 mL/minute) from OASIS. Methods: 655 patients were randomized 1:1 to OMC 100 mg IV q12h × 2 doses then 100 mg IV q24h, or to LZD per label. After ≥ 3 days' IV therapy, patients could transition to oral OMC 300 mg q24h or oral LZD. Total treatment period was 7–14 days. Primary endpoint was early clinical response (ECR) assessed 48–72 hours after IV therapy in the modified intent-to-treat (mITT) population. Secondary endpoints were investigator-assessed clinical success at post-treatment evaluation (PTE) in the mITT and clinically evaluable (CE) populations. Safety was assessed based on adverse events (AEs), vital signs, and laboratory tests. 522 patients in the safety population had CKD-1; 119 had CKD-2/3. Results: Table 1. ECR-mITT Population Conclusion: In patients with CKD, IV to once-daily oral OMC was comparable to IV to twice-daily oral LZD for the treatment of ABSSSI. OMC was safe and well-tolerated with similar AEs to those without CKD. Disclosures: N. Cure-Bolt, Paratek Pharmaceuticals: Employee and Shareholder, Salary; S. Chitra, Paratek Pharmaceuticals: Employee and Shareholder, Salary; E. Tzanis, Paratek Pharmaceuticals: Employee and Shareholder, Salary; P. McGovern, Paratek Pharmaceuticals: Employee and Shareholder, Salary.